Utilizing music and songs to promote student engagement in ESL classrooms - Bokiev, Daler; Bokiev, Umed (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
One of the main challenges English language teachers face in their daily classes is to find creative ways of sustaining their students’ interest in language learning, which can often be perceived as dull and tedious. Music and songs, which have a universal appeal and ubiquitous presence in most people’s daily lives, have all the prerequisites to become an effective teaching resource in this respect. However, this useful resource appears to be underutilized by English language teachers, which is attributable to the lack of understanding of its theoretical rationale and benefits. The present paper aims to examine the role and potential of music and songs in English language teaching in the light of current literature. Research findings suggest that the effective use of music and songs in language teaching has the potential to address multiple intelligences, reduce anxiety, increase motivation, facilitate memory retention and establish an affectively conducive learning environment. Moreover, music and songs can be utilized to enhance the learning of almost every aspect of the target language, to develop cultural awareness and to foster students’ creativity. Apart from adducing theoretical arguments and empirical evidence in support of using music and songs in language instruction, the paper provides practical suggestions for integrating music activities into ESL classrooms. It is hoped that a larger number of ESL teachers will deem music and songs a valuable educational tool which they can use to engage their students both affectively and cognitively, promoting enjoyable and effective language teaching and learning.